Analisis Pengendalian Mutu Susu Pasteurisasi Pada Produk Usaha TwinMilk - Vadia Lubna Chalisa; Paulina Gabriella Lois Saroinsong; Dhiya Shafa Maulida; Putra Ramadhan; Renaldi Putra (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the quality of pasteurized milk products at the Twinmilk business in Sukabumi using quality control tools such as checksheets, Pareto diagrams, and fishbone diagrams. Twinmilk is a cow's milk processing business originating from the Cinta Priangan group under the auspices of the Gemah Ripah Cooperative. In the production process, this business faces various common problems such as packaging damage, handling errors, and product contamination that can reduce the quality of pasteurized milk. This study uses a quantitative descriptive method with primary data obtained through interviews and direct observation. The results show that the most dominant type of product damage is leaking and damaged packaging (55%), followed by contamination during packaging (30%), and milk texture or color that does not meet standards (15%). Based on the fishbone analysis, the main causal factors come from human aspects, machines, methods, raw materials, and measurements that are not optimal. This study recommends improving workforce training, pasteurization equipment maintenance, and monitoring the cleanliness of raw materials and packaging to ensure product quality remains consistent and meets standards.